Cases on higher education spaces innovation, collaboration, and technology - Carpenter, Russell G. (Information Science Reference, 2013)
"This book highlights key innovations and collaborative ventures in space design from across campuses and institutions, including writing and communication centers, studios, libraries, digital media labs, learning commons, and academic learning spaces" - Provided by publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung